The impact of service quality dimension towards customer satisfaction at Melaka International Trade Centre / Nur Fitra Azira Yusop - Yusop, Nur Fitra Azira (Faculty of Business and Management, 2018)
The purpose of the study is to identify the relationship between customer satisfaction and service quality dimension at event organizing by MITC. A survey were conducted amongst the customers who make a reservation at Buffet Ramadhan MITC. In this study, there are four (4) factors were adopted which is responsiveness, tangibility, assurance and reliability. This factor will be analyses whether there is a significant relationship with customer satisfaction or not. A total of 125 of respondent were selected randomly using a convenience sampling. The finding shows that, there is a significant relationship between service quality dimension and customer satisfaction. And some recommendation were provided by the researcher for the future research about the service quality dimensions.